Bringing Out-of-School Learning into the Classroom: Self- versus Peer-Monitoring of Learning Behaviour - Yelva C. Larsen; Jorge Groß; Franz X. Bogner (MDPI AG, 2020)
Based on classroom management fostering autonomy support and intrinsic motivation, this study examines effects of reciprocal peer-monitoring of learning behaviours on cognitive and affective outcomes. Within our study, 470 German secondary school students between 13 and 16 years of age participated in a multimodal hands- and minds-on exhibition focusing on renewable resources. Three groups were separated and monitored via a pre-post-follow up questionnaire: the first conducted peer-monitoring with the performance of specific roles to manage students' learning behaviours, the second accomplished a self-monitoring strategy, while the third group did not visit the exhibition. In contrast to the latter control group, both treatment groups produced a high increase in short- and long-term knowledge achievement. The peer-monitored group scored higher in cognitive learning outcomes than the self-monitored group did. Interestingly, the perceived level of choice did not differ between both treatment groups, whereas peer-monitoring increased students' perceived competence and simultaneously reduced the perceived level of anxiety and boredom. Peer-monitoring realised with the performance of specific roles seems to keep students "on task" without lowering indicators for students' intrinsic motivation. Herewith, we are amongst the first to suggest peer-monitoring as a semi-formal learning approach to balance between teacher-controlled instruction and free-choice exploration.